2022
DOI: 10.21037/atm-21-6158
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics for predicting revised hematoma expansion with the inclusion of intraventricular hemorrhage growth in patients with supratentorial spontaneous intraparenchymal hematomas

Abstract: Background: Previous radiomics analyses of hematoma expansion have been based on the traditional definition, which only focused on changes in intraparenchymal volume. However, the ability of radiomicsrelated models to predict revised hematoma expansion (RHE) with the inclusion of intraventricular hemorrhage expansion remains unclear. To develop and validate a noncontrast computed tomography (NCCT)-based clinical-semantic-radiomics nomogram to identify supratentorial spontaneous intracerebral hemorrhage (sICH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(58 reference statements)
0
7
0
1
Order By: Relevance
“…Patients with ICH continue to bleed after the initial hemorrhage, known as hematoma expansion (HE) which is a well-established independent predictor of clinical deterioration [ 12 ]. HE represents a plausible therapeutic target in many clinical trials due to the characteristic of being potentially preventable and as such, is a very important outcome predictor [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with ICH continue to bleed after the initial hemorrhage, known as hematoma expansion (HE) which is a well-established independent predictor of clinical deterioration [ 12 ]. HE represents a plausible therapeutic target in many clinical trials due to the characteristic of being potentially preventable and as such, is a very important outcome predictor [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with ICH continue to bleed after the initial hemorrhage, known as hematoma expansion (HE) which is a well-established independent predictor of clinical deterioration [ 12 ]. HE represents a plausible therapeutic target in many clinical trials due to the characteristic of being potentially preventable and as such, is a very important outcome predictor [ 12 ]. HE is defined as a more than 33% increase in ICH volume within the first 24 h resulting in significant neurological deficits and enhancement of ICH-induced primary and secondary brain injury [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4A presents a network plot of the indicators involved in the composition. In the NMA, 846 patients from five articles were included ( 4 , 6 , 7 , 21 , 22 ). The results synthesized according to Bayesian NMA revealed that the predictive ability of the radiomics model outperformed most of the NCCT biomarkers ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies comprising a total of 1525 patients were quantitatively analyzed for hematoma expansion after cerebral hemorrhage using the radiomics method (4,6,7,(17)(18)(19)(20)(21)(22)(23). The pooled Se, Sp, PPV, NPV, and DAR were 0.771 (0.710-0.832), 0.743 (0.684-0.801), 0.612 (0.448-0.737), 0.863 (0.815-0.912), and 0.748 (0.707-0.788), respectively (Figure 3).…”
Section: Diagnostic Test Meta-analysis 411 Radiomics Modelmentioning
confidence: 99%
“…These compounds have extremely high potential for clinical applications. Various other technologies have also been used to predict hemorrhagic growth [ 26 27 ]. The performance of the radiomics model proposed by Xia et al [ 26 ] was significantly better than the NCCT signs obtained in our study.…”
Section: Discussionmentioning
confidence: 99%